OPTIMAL NETWORK PLANNING USING EVOLUTIONARY ALGORITHMS - Mayta H., Rosmeri (2003)
This article proposes using Multi- Targeted Evolutionary Algorithms for Telephone Exchange Planning, on the short, medium and long run. Experimental resuls for a city make the present proposal valuable because of the quick, varied and quality solutions obtained.